#### Answer

See answers below

#### Work Step by Step

A) $\frac{\sqrt 2}{\sqrt 3}$
Multiplying the equation by $\frac{\sqrt3}{\sqrt3}$
$=\frac{\sqrt 2.\sqrt 3}{3}$
$=\frac{\sqrt 6}{3}$
B) $\frac{\sqrt 5}{\sqrt 18m}$
Multiplying the equation by $\frac{\sqrt 18m}{\sqrt 18m}$
$=\frac{\sqrt 5.\sqrt 18m}{\sqrt (18m)^2}$
$=\frac{\sqrt 90m}{18m}$
$=\frac{3\sqrt 10m}{18m}$
$=\frac{\sqrt 10m}{6m}$
C) $\sqrt \frac{7s}{3}=\frac{\sqrt 7s}{\sqrt 3}$
Multiplying the equation by $\frac{\sqrt3}{\sqrt3}$
$=\frac{\sqrt 7s.\sqrt 3}{3}$
$=\frac{\sqrt 21s}{3}$